Cost effectiveness of ergonomic redesign of electronic motherboard - Sen, Rabindra Nath; Yeow, Paul H. P. (Elsevier Science, 2003)
A case study to illustrate the cost effectiveness of ergonomic redesign of electronic motherboard was presented. The factory was running at a loss due to the high costs of rejects and poor quality and productivity. Subjective assessments and direct observations were made on the factory. Investigation revealed that due to motherboard design errors, the machine had difficulty in placing integrated circuits onto the pads, the operators had much difficulty in manual soldering certain components and much unproductive manual cleaning (MC) was required. Consequently, there were high rejects and occupational health and safety (OHS) problems, such as, boredom and work discomfort. Also, much labour and machine costs were spent on repairs. The motherboard was redesigned to correct the design errors, to allow more components to be machine soldered and to reduce MC. This eliminated rejects, reduced repairs, saved US $581,495/year and improved operators' OHS. The customer also saved US $142,105/year on loss of business. (C) 2003 Elsevier Ltd. All rights reserved.